The Alpha-Melanocyte Stimulating Hormone Induces Conversion of Effector T Cells into Treg Cells - Andrew W. Taylor; Darren J. Lee (Journal of Transplantation)
The neuropeptide alpha-melanocyte stimulating hormone (α-MSH) has an important role in modulating immunity and homeostasis. The production of IFN-γ by effector T cells is suppressed by α-MSH, while TGF-β production is promoted in the same cells. Such α-MSH-treated T cells have immune regulatory activity and suppress hypersensitivity, autoimmune diseases, and graft rejection. Previous characterizations of the α-MSH-induced Treg cells showed that the cells are CD4+ T cells expressing the same levels of CD25 as effector T cells. Therefore, we further analyzed the α-MSH-induced Treg cells for expression of effector and regulatory T-cell markers. Also, we examined the potential for α-MSH-induced Treg cells to be from the effector T-cell population. We found that the α-MSH-induced Treg cells are CD25+  CD4+ T cells that share similar surface markers as effector T cells, except that they express on their surface LAP. Also, the α-MSH treatment augments FoxP3 message in the effector T cells, and α-MSH induction of regulatory activity was limited to the effector CD25+ T-cell population. Therefore, α-MSH converts effector T cells into Treg cells, which suppress immunity targeting specific antigens and tissues.